DETERMINING THE EFFECTIVE RATE OF INTEREST ON A SERIES OF BONDS. - Byerly, Richard A. (The Accounting Review, 1941)
The article presents ways to determine effective rate of interest on series of bonds. The article also demonstrates a rather simple mathematical system, which will give the required rate as accurately as desired and which will eliminate a great deal of the guesswork and labor in estimating charges of this type. No difficulty arises when dealing with one bond, or a group of bonds due on a single date, or in the simpler cases, since Makeham's formula or other methods in current use will serve satisfactorily. An accountant must choose from a number of arbitrary methods and be satisfied with approximations, or resort to a tedious trial and error method for establishing the true rate of interest effective in the case under consideration. A purchaser of bonds may be willing to supply information relative to the basis of his bid of premium or discount, and hence furnish an initial approximation to the rate required. Because of various factors, the information would never be sufficiently accurate for the purposes the accountant has in mind.